The magnitude of intimate partner violence during pregnancy in Eldoret, Kenya: exigency for policy action. (9th November 2020) - Luhumyo, Loice; Mwaliko, Emily; Tonui, Philliph; Getanda, Amos; Hann, Katrina
Abstract: Intimate partner violence (IPV) is sexual, psychological and physical coercive acts used against persons by intimate partners. When IPV occurs during pregnancy (IPVp), it can result in adverse maternal and pregnancy outcomes. No policy nor practice direction exists to address the rates and risk factors of IPVp in Kenya. Determining the prevalence, types and determinants of IPVp in Western Kenya would aid in the identification of pregnant women affected by and/or at risk of IPVp, as well as informing the development of policy, practices and programmes to support preventive interventions. In this cross-sectional study of 369 women who had given birth at Moi Teaching and Referral Hospital, participants were recruited using systematic sampling and data collected via structured questionnaires adopted from the WHO Violence Against Women Instrument. Associations were made in relation to physical or sexual violence and psychological violence. Logistic regression was used to assess the association between determinants and occurrence of IPVp. The overall prevalence of IPVp was 34.1%. Prevalence of physical or sexual violence was 22.8%. Psychological violence emerged as the most common (27.4%) form of IPVp. A lower than tertiary level of education and previous experience of IPV were individually associated with physical/sexual IPVp, whereas psychological IPVp was associated with previous experience of IPV and was prevented by the intimate partner having formal employment. Preterm birth rates were found to be higher than the country's rates. The prevalence rates of IPVp are high in Western Kenya. Strategies that address the promotion of respectful, nonviolent relationships and that interrupt the development of risk factors are required. Policies (clinical guidelines) targeting prevention of IPVp and screening and the identification of at-risk women and survivors of IPVp are needed urgently. Primary prevention through interrupting the occurrence of predisposing factors is key in addressing IPVp.